ARM2GC: Succinct Garbled Processor for Secure Computation - Songhori, Ebrahim M.; Riazi, M. Sadegh; Hussain, Siam U.; Sadeghi, Ahmad-Reza; Koushanfar, Farinaz (Proceedings of the 56th Annual Design Automation Conference 2019, 2019)
We present ARM2GC, a novel secure computation framework based on Yao's Garbled Circuit (GC) protocol and the ARM processor. It allows users to develop privacy-preserving applications using standard high-level programming languages (e.g., C) and compile them using off-the-shelf ARM compilers, e.g., gcc-arm. The main enabler of this framework is the introduction of SkipGate, an algorithm that dynamically omits the communication and encryption cost of a gate when its output is independent of the private data. SkipGate greatly enhances the performance of ARM2GC by omitting costs of the gates associated with the instructions of the compiled binary, which is known by both parties involved in the computation. Our evaluation on benchmark functions demonstrates that ARM2GC outperforms the prior best solution by 156 × .CCS CONCEPTS* Security and privacy → Privacy-preserving protocols;